A 1.7‐Mb chromosomal inversion downstream of a PpOFP1 gene is responsible for flat fruit shape in peach. Issue 1 (17th August 2020) - Zhou, Hui; Ma, Ruijuan; Gao, Lei; Zhang, Jinyun; Zhang, Aidi; Zhang, Xiujun; Ren, Fei; Zhang, Weihan; Liao, Liao; Yang, Qiurui; Xu, Shengli; Otieno Ogutu, Collins; et al.
Abstract: Flat peaches have become popular worldwide due to their novelty and convenience. The peach flat fruit trait is genetically controlled by a single gene at the S locus, but its genetic basis remains unclear. Here, we report a 1.7‐Mb chromosomal inversion downstream of a candidate gene encoding OVATE Family Protein, designated PpOFP1, as the causal mutation for the peach flat fruit trait. Genotyping of 727 peach cultivars revealed an occurrence of this large inversion in flat peaches, but absent in round peaches. Ectopic overexpression of PpOFP1 resulted in oval‐shaped leaves and shortened siliques in Arabidopsis, suggesting its role in repressing cell elongation. Transcriptional activation of PpOFP1 by the chromosomal inversion may repress vertical elongation in flat‐shaped fruits at early stages of development, resulting in the flat fruit shape. Moreover, PpOFP1 can interact with fruit elongation activator PpTRM17, suggesting a regulatory network controlling fruit shape in peach. Additionally, screening of peach wild relatives revealed an exclusive presence of the chromosomal inversion in P. ferganensis, supporting that this species is the ancestor of the domesticated peach. This study provides new insights into mechanisms underlying fruit shape evolution and molecular tools for genetic improvement of fruit shape trait in peach breeding programmes.